LITERASI DIGITAL GURU DALAM KONTEKS PENDIDIKAN ISLAM: ANALISIS SISTEMATIS ATAS KESIAPAN SDM DALAM MENGHADAPI ERA PENDIDIKAN 5.0: Teachers' Digital Literacy in the Context of Islamic Education: A Systematic Analysis of Human Resource Readiness in Facing the Era of Education 5.0 - Syaharuddin, Syaharuddin; M. Anugrah Arifin; Fathurrijal, Fathurrijal; Rahmawati, Endang; Ishanan, Ishanan (TA'LIMUNA: Jurnal Pendidikan Islam, 2025)
The transformation of education towards the Education 5.0 era requires human resources, especially teachers, to be prepared in mastering digital literacy that is in line with Islamic values. This study aims to systematically review literature discussing teacher digital literacy in the context of Islamic education, with a focus on the level of Human Resource (HR) readiness in responding to the challenges of the Education 5.0 era. Using a qualitative method with a Systematic Literature Review (SLR) approach, this study traces publications from the DOAJ, Scopus, and Google Scholar databases published between 2015 and 2025. The findings indicate that the readiness of Islamic education HR is still in a transitional phase and is not yet evenly distributed among individuals and institutions. Although there have been efforts to integrate digital technology in alignment with Islamic values by some teachers and institutions, its implementation is generally still limited to technical and administrative aspects. Digital literacy has not yet been fully internalized as part of strategic, reflective, and transformative pedagogical reform. These findings underscore the importance of strengthening digital literacy training based on Islamic values, as well as the need for institutional policies and visionary leadership that support the sustainable integration of technology in Islamic education. Transformasi pendidikan menuju era Pendidikan 5.0 menuntut kesiapan sumber daya manusia, terutama guru, dalam menguasai literasi digital yang selaras dengan nilai-nilai keislaman. Penelitian ini bertujuan mengkaji secara sistematis literatur yang membahas literasi digital guru dalam konteks pendidikan Islam, dengan fokus pada tingkat kesiapan Sumber Daya Manusia (SDM) dalam merespons tantangan era Pendidikan 5.0. Menggunakan metode kualitatif dengan pendekatan Systematic Literature Review (SLR), studi ini menelusuri publikasi dari database DOAJ, Scopus, dan Google Scholar yang diterbitkan antara tahun 2015 hingga 2025. Hasil telaah menunjukkan bahwa kesiapan SDM pendidikan Islam masih berada pada fase transisional dan belum merata antar individu maupun lembaga. Meskipun terdapat upaya integrasi teknologi digital yang selaras dengan nilai-nilai keIslaman oleh sebagian guru dan institusi, penerapannya secara umum masih terbatas pada aspek teknis dan administratif. Literasi digital belum sepenuhnya diinternalisasi sebagai bagian dari reformasi pedagogis yang strategis, reflektif, dan transformatif. Temuan ini menegaskan pentingnya penguatan pelatihan literasi digital berbasis nilai Islam serta kebijakan kelembagaan dan kepemimpinan visioner yang mendukung integrasi teknologi dalam pendidikan Islam secara berkelanjutan. Kata Kunci :  Era Pendidikan 5.0; Literasi Digital Guru; Pendidikan Islam; Sumber Daya Manusia.